Analysis of the attractiveness of the Polish market for venture capital funds - Katarzyna Wierzbicka; Anna Gardocka-Jałowiec (e-Finanse: Financial Internet Quarterly, 2017)
The purpose of this article is to present the factors and phenomena resulting from the interaction of economic entities (entrepreneurs and consumers), which determine the level of investment attractiveness for venture capital funds. The activities are aimed at identifying which sectors and sectors of the economy in Poland may in future draw a growing interest of venture capital investors. They conclude that in the long run, consumer values and expectations will have a far greater impact than the technological change itself, on the process of building a market position and on the management of an enterprise. It is concluded that the Polish economy, as a result of demographic change, globalization and technology, will appear as an attractive area for venture capital investment. The basis of the discussion is Polish and foreign literature on the subject, current reports and statistical data.
Keywords: D15; D21; D25; O30; 330; venture capital; investment attractiveness; innovation; consumption